Importance of adsorption compared with complexation for retarding C3S hydration via adding sodium gluconate - Luo, Guitao (2025)
Adsorption effect on particle surfaces and complexation effect with free Ca2+ mostly determine the retarding performance of organic admixtures on cement hydration. However, it is difficult to identify which effect plays a more important role in retarding hydration by experimental methods. Here, a theoretical model was developed to investigate the retarding mechanisms of sodium gluconate (SG) on hydration of tricalcium silicate (C3S). Based on obstruction theory and complexation reaction kinetics, effects of adsorption and complexation were simulated to examine the retarding performance of C3S hydration with addition of SG. The proposed model well predicted the effect of additional dosing of SG on the retarding performance of C3S hydration. Theoretical parameter studies demonstrated that adsorption ratio contributed much largely to the delays in C3S hydration, compared with rate constant of complex generation. Therefore, it is confirmed that adsorption plays a more important role in regulating the retarding mechanism of C3S hydration.